Cardiac Time Intervals Derived from Electrocardiography and Seismocardiography in Different Patient Groups - Elnaggar Ismail; Pykäri Jouni; Hurnanen Tero; Lahdenoja Olli; Airola Antti; Kaisti Matti; Vasankari Tuija; Savontaus Mikko; Koivisto Tero (United States, 2025)
Differences in cardiac time intervals (CTIs) have previously been shown in different patient groups with varying levels of cardiac function. These studies relied on methods such as conventional echocardiography or tissue doppler imaging performed by a specialist to extract CTIs. The goal of this study was to evaluate the ability of using a combination of single lead ECG and 3-axis seismocardiography (SCG) from a sensor placed on a subject’s sternum to automatically extract CTIs.
For each subject, pre-ejection period (PEP), left ventricular ejection time (LVET), total systolic time (TST), and total diastolic time (TDT), which were normalized by the mean heart rate representing the entire recording were extracted using a custom developed algorithm.
LVET was on average 20.5 % shorter in the NKHCD group vs PRE-TAVI (p < 0.05) and 5.9% shorter in the HCD group vs PRE-TAVI (p > 0.05). Comparing CTIs between the subjects who had data recorded before and after receiving a TAVI procedure, a 12.6% postoperative reduction in LVET (p < 0.05) was found on average as well as a 30.2% increase in PEP/LVET (p < 0.05). These results are in line with literature where LVET increases with age and severe aortic stenosis and decreases after TAVI procedures when echocardiography was the main methodology used to extract CTIs.
Computing in Cardiology 2022